This last equality can be justified as follows:
(1) write
\begin{equation*}
X_{n,k}=\frac{(-1)^{k-1}}{k^{2}\binom{n+k}{k}\binom{n-1}{k}},\qquad D_{n,k}=\frac{(-1)^{k}}{n^{2}\binom{n+k}{k}\binom{n-1}{k}}\qquad k<n;
\end{equation*}
(2) notice that $X_{n,k}=D_{n,k-1}-D_{n,k}$, and (3) sum over $k$, $1\leq
k\leq n-1$
\begin{equation*}
\sum_{k=1}^{n-1}X_{n,k}=\sum_{k=1}^{n-1}\left( D_{n,k-1}-D_{n,k}\right)
=D_{n,0}-D_{n,n-1}.
\end{equation*}
(4) Finally, sum over $n$, $1\leq n\leq N$, because
\begin{equation*}